The Effect of Locally Produced Unstable Shoes on Foot Plantar Pressure During Walking Among Healthy Male Students - Siavash Etemadi Nejad; Saed Ahmadi Ganjeh; Jamshid Yazdani CHarati; Esmail Hoseini Nejad (Biyumikānīk-i varzishī, 2018)
Objective Today, various shoes have been developed to reduce injury and improve performance during walking. The aim of this study was to evaluate the effect of locally produced unstable shoes on foot plantar pressure during walking in healthy male students. Methods Participants were 20 healthy male students (Mean±SD of height=178.96±3.92 cm, Mean±SD of age=27±3 years, Mean±SD of mass=73.99±6.6 kg and EU shoe size=42). They were evaluated under four wearing conditions: Locally produced unstable shoes, unstable shoes produced abroad, regular control shoes, and barefoot. The maximum foot plantar pressure was measured in ten plantar areas by a footscan system while walking. The generalized linear model and repeated measures Analysis of Variance (ANOVA) and/or Friedman test at a significance level of 0.05 (P<0.05) were used for analyzing data using SPSS V. 23 software. Results Maximum foot plantar pressure during walking under four different conditions was significantly different only in three plantar regions of hallux, lesser digits, and metatarsal 5 (P<0.05). Conclusion Suggest the inefficiency of unstable shoes manufactured in Iran in adjusting the plantar pressure in individuals.